A cellulose liquid crystal motor: A steam engine of the second kind - Geng, Yong (2013)
We acknowledge support from the Portuguese Science and Technology Foundation through grants SFRH/BD/63574/2009, SFRH/BPD/78430/2011 to Y. Geng and S.N. Fernandes respectively, projects PTDC/CTM/099595/2008, PTDC/FIS/110132/2009, PEst-C/CTM/LA0025/2011 (Strategic Project - LA 25 - 2011-2012) and from the U.S. National Science Foundation IIP 1114332.